2021
DOI: 10.1039/d1gc00515d
|View full text |Cite
|
Sign up to set email alerts
|

Protic ionic liquids from di- or triamines: even cheaper Brønsted acidic catalysts

Abstract: Dicationic and tricationic ionic liquids, synthesised by proton trasfer from sulfuric acid and corresponding di- and triamines, were characterised and used as Brønsted acidic catalysts in the biodiesel production. It...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…1 This simple synthetic pathway makes them much cheaper than aprotic ionic liquids (AIL) and hence suitable for large-scale commercial applications. 2,3 One further key feature, in contrast to AILs, is the proton availability for transfer reactions due to the presence of proton donor/proton acceptor sites. This property also allows for the formation of extensive hydrogen bond networks 4 and makes PILs promising candidates as electrolytes in fuel cells and in catalysis.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 This simple synthetic pathway makes them much cheaper than aprotic ionic liquids (AIL) and hence suitable for large-scale commercial applications. 2,3 One further key feature, in contrast to AILs, is the proton availability for transfer reactions due to the presence of proton donor/proton acceptor sites. This property also allows for the formation of extensive hydrogen bond networks 4 and makes PILs promising candidates as electrolytes in fuel cells and in catalysis.…”
Section: ■ Introductionmentioning
confidence: 99%
“…An interesting, but hitherto not much studied subset of ILs are protic ionic liquids (PILs), which are prepared through the stoichiometric neutralization of a strong Brønsted acid with a strong Brønsted base . This simple synthetic pathway makes them much cheaper than aprotic ionic liquids (AIL) and hence suitable for large-scale commercial applications. , One further key feature, in contrast to AILs, is the proton availability for transfer reactions due to the presence of proton donor/proton acceptor sites. This property also allows for the formation of extensive hydrogen bond networks and makes PILs promising candidates as electrolytes in fuel cells and in catalysis. , The PIL addressed in the present investigation, diethylmethylammonium trifluoromethanesulfonate, [dema]­[TfO] (Figure ), e.g., enables reliable O 2 reduction conditions due to its high and stable open-circuit potential combined with a wide liquid temperature range and high thermal stability …”
Section: Introductionmentioning
confidence: 99%
“…22 Using sulfuric acid in excess with respect to the base yields highly Bro̷ nsted acidic ILs and further lowers the cost, which can be decreased even more by the use of diamines and triamines instead of monoamines. 23,24 As we estimated in 2021, 23 the laboratory-scale synthesis cost of PILs from diethylenetriamine and bis(hexamethylene)triamine can be as low as $31.6 and $68.9 kg −1 , respectively (for the estimation, the updated prices available directly from the Merck catalogue were taken), 25 whereas the cost of 1,4-butanosultone reagent used for the synthesis of sulfonic acid-functionalized ILs is $129 per 100 g. Moreover, modulating the ratio of sulfuric acid to base, as well as the structures of di/triamines, allows for finetuning of the physicochemical parameters of ILs, such as acidity, viscosity, and density. 23 In our earlier study, we reported on the Beckmann rearrangement of oximes catalyzed with Bro̷ nsted-acidic PILs that were synthesized from sulfuric acid and monoamines.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, CO 2 -reactive ILs could efficiently catalyze the transformation of CO 2 under mild and metal-free conditions due to the synergistic effect of the IL anion activating CO 2 by forming carbamate intermediates and the cation activating the substrates by forming hydrogen bonds. 27 The IL cation as a hydrogen bond donor and the IL anion as a hydrogen bond acceptor could cooperatively achieve various chemical reactions under metal-free conditions, including alcohol dehydration, 28 alcohol oxidative esterification, 29 and ring-closing metathesis of aliphatic diethers to O-heterocycles. 30 Herein, we report a hydrogen-bonding and acid cooperative catalysis strategy for the benzylation of arenes with benzyl alcohols over Brønsted acid ILs (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%